Health care provider perspectives on cervical screening for Aboriginal and Torres Strait Islander women: a qualitative study. (8th March 2021) - Jaenke, Rachael; Butler, Tamara L.; Condon, John; Garvey, Gail; Brotherton, Julia M.L.; Cunningham, Joan; Anderson, Kate; Tong, Allison; Moore, Suzanne P.; Whop, Lisa J.
Abstract: Objective : To investigate perspectives of primary health care providers (HCPs) on providing cervical screening for Aboriginal and Torres Strait Islander women, who experience a higher burden of cervical cancer than other Australian women. Methods : Semi‐structured interviews with 13 HCPs from four Australian Indigenous primary health care centres (PHCCs). Transcripts were thematically analysed. Results : HCPs discussed the need to approach cervical screening with sensitivity to women's emotional and cultural needs and sustaining relationships built on trust and respect. HCPs reported challenges in promoting screening to Aboriginal and Torres Strait Islander women due to cumbersome systems, competing clinical priorities, workforce capacity limitations and specific challenges associated with implementing the renewed National Cervical Screening Program. Conclusions : In practice, HCPs experience several challenges to delivering cervical screening. Understanding HCPs' perspectives on their approach to cervical screening delivery, and the systems in which this occurs, can help to ensure that they receive adequate support and resources to deliver cervical screening to Aboriginal and Torres Strait Islander women. Implications for public health : It is important that HCPs adopt a multi‐faceted, person‐centred approach to cervical screening that is responsive to women's needs and that works synchronously with supportive PHCC services and systems and the National Cancer Screening Register.